Intervening to reduce the risk of future disability from multiple sclerosis: are we there yet?. (3rd October 2017) - Dahdaleh, Maurice; Alroughani, Raed; Aljumah, Mohammed; AlTahan, Abdulrahman; Alsharoqi, Issa; Bohlega, Saeed A; Daif, Abdulkader; Deleu, Dirk; Inshasi, Jihad; Karabudak, Rana; Sahraian, Mohammed A.; Taha, Karim; et al.
ABSTRACT: Disease-modifying therapies (DMTs) delay or may prevent the progression of patients with high-risk clinically isolated syndrome (CIS) to clinically definite multiple sclerosis (MS), and from relapsing–remitting MS to secondary progressive MS. Current evidence on the effects of DMT on disability in MS is supported by the use of the Expanded Disability Status Scale (EDSS), which is dominated by ambulation, and usually used as a secondary outcome measure. Less is known about the long-term effects of DMTs on other aspects of functional status, particularly cognition, which is a key determinant of ability to work. The time scale for measurements of disability is at most a few years, with scant data from more than 10 years of observation. Longer prospective follow-up of large numbers of patients with CIS is needed to determine whether early intervention with a DMT influences long-term disease progression. Finally, the emergence of the radiologically isolated syndrome (RIS) as a clinical entity has shifted the debate about when to intervene to an even earlier time frame. Balancing the significant side-effects associated with DMT in general and the expected outcome of pharmacologic intervention is increasingly problematic for managing patients with uncertain prognosis, as many patients may have low-risk CIS, benign MS or patients with RIS only. Preventing long-term disability in MS should be recognised more clearly as an important outcome in its own right, with disability measured more consistently with more sensitive instruments beyond the use of the EDSS.